Methodologies and intelligent systems for technology enhanced learning : 7th International Conference - Vittorini, Pierpaolo; Gennari, Rosella; Di Mascio, Tania; Rodriguez, Sara; De la Prieta, Fernando; Ramos, Carlos; Silveira, Ricardo Azambuja (Springer, 2017)
This book presents the outcomes of the 7th International Conference in Methodologies and Intelligent Systems for Technology Enhanced Learning (MIS4TEL'17), hosted by the Polytechnic of Porto, Portugal from 21 to 23 June 2017. Expanding on the topics of the previous conferences, it provided an open forum for discussing intelligent systems for technology enhanced learning (TEL) and their roots in novel learning theories, empirical methodologies for their design or evaluation, stand-alone and web-based solutions, and makerspaces. It also fostered entrepreneurship and business startup ideas, bringing together researchers and developers from industry, education and the academic world to report on the latest scientific research, technical advances and methodologies.
Includes author index.
Keywords: Educational technology -- Congresses.; Educational innovations -- Congresses.; elektronické knihy; electronic books